Wave Power Absorption by Arrays of Wave Energy Converters in Front of a Vertical Breakwater: A Theoretical Study - Dimitrios N. Konispoliatis; Spyridon A. Mavrakos (Energies, 2020)
The present paper deals with the theoretical evaluation of the efficiency of an array of cylindrical Wave Energy Converters (WECs) having a vertical symmetry axis and placed in front of a reflecting vertical breakwater. Linear potential theory is assumed, and the associated diffraction and motion radiation problems are solved in the frequency domain. Axisymmetric eigenfunction expansions of the velocity potential are introduced into properly defined ring-shaped fluid regions surrounding each body of the array. The potential solutions are matched at the boundaries of adjacent fluid regions by enforcing continuity of the hydrodynamic pressures and redial velocities. A theoretical model for the evaluation of the WECs’ performance is developed. The model properly accounts for the effect of the breakwater on each body’s hydrodynamic characteristics and the coupling between the bodies’ motions and the power take-off mechanism. Numerical results are presented and discussed in terms of the expected power absorption. The results show how the efficiency of the array is affected by (a) the distance between the devices and the wall, (b) the shape of the WEC array configuration, as well as (c) the angle of the incoming incident wave.